Android-Based Learning Media Of Kawi Language - Ni Nengah Turita Sari; Ketut Artaye (Proceeding International Conference on Information Technology and Business, 2019)
The development of science and technology is increasingly driving renewal efforts in the use of technological outcomes in the teaching and learning process. Interactive and interesting learning media can increase, direct, and focus students’ attention on material taught by lecturers. Kawi Language is one of the courses at the Sekolah Tinggi Agama Hindu (STAH) Lampung. However, in the learning process, there are still many educators who do not know the benefits of learning media and there are not many educators who can choose effective and enjoyable media in the learning process. Therefore, by utilizing the current technological development, Android, it can be used as an alternative learning media that can be accessed anytime and anywhere.The research method used is Prototype. The output of this study is a learning media application of Kawi Language which is interactive and can be accessed via an Android smartphone. This application is created using Android Studio. By using this learning media, students can learn effectively through an Android smartphone easily. Based on several stages of the trial, the learning media is categorized as valid with good criteria. This study is expected to be useful for lecturers, students, and advanced researchers.Keywords: Learning Media, Android, Kawi Language